Simple and Effective Design Concept for Constructing In-Situ Soil Dielectric Property Sensor With Dual Low-Cost COTS Microwave Modules - Prapan Leekul; Bonny Mgawe; Twahir Kazema; Hoang Nam Dao; Phaophak Sirisuk; Monai Krairiksh (IEEE Access, 2022)
This paper presents a compact sensor system for estimating the dielectric properties of materials based on commercial, off-the-shelf (COTS) modules. The dielectric constant and conductivity of a material under test can be determined from the measurement of the microwave reflected from the material. By using dual microwave sensor modules with a slightly different radio frequency, an identical intermediate frequency at the mixers of the modules was obtained. The intermediate frequency was chosen such that the associated microwave and data processing components could be easily obtainable, leading to a practical realization of the sensor system. Synchronization of the two microwave sensor modules was achieved using electronically controlled relays that simultaneously switch on the power supplies of both modules. Two microcontrollers were used to capture the corresponding signals. The sensor was designed at a 10 GHz band for measuring reflected waves from various kinds of materials, especially soils with different moisture and fertilizer contents. The evaluation results indicate a good agreement between the measured results from the proposed sensor and the ones from a network analyzer, verifying that the proposed sensor is fully functional for monitoring variation in the dielectric properties of materials, including soil. The average sensitivity for the dielectric constant of moist soil is 0.26/% moisture content and the error rate for dielectric constant measurement is 4.83%.
Keywords: Soil Moisture and Remote Sensing; Microwave and Dielectric Measurement Techniques; Microwave Engineering and Waveguides